(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Linguistic research has paid insufficient attention to the terminology related to agricultural rice cultivation activities in Uzbekistan. Studies cover agricultural terminology but a full semantic classification of Uzbek rice farm vocabulary does not exist currently. This research fills a knowledge gap through its analysis of rice cultivation terminology that classifies the terms into functional groups of lexical-semantic groups (LSGs). The researchers collected agricultural data through descriptive and analytical methods by studying texts, dictionaries along with conducting field research. The research identified 35 different LSGs that cover irrigating, cultivation and harvesting steps in addition to terms for soil preparation methods and processing as well as storage techniques. Uzbek rice farming terminology manifests through a combination of traditional agricultural practices along with geographical linguistic differences and contemporary technological progression. The analysis shows how the study uncovers the network of linguistic relationships between agricultural discourse components which demonstrates their adherence to broader syntactic and semantic relationships. Research outcomes help explain specialized vocabulary organization through explanations of semantic systems that shape lexical creation in agriculture. The findings contribute practical value for all three domains: linguistic preservation alongside agricultural education and terminology standardization which assists farmers and linguists and policymakers to develop sustainable agricultural terms. This study explores Uzbek rice farming terminology to enhance later linguistic and agricultural research that will connect language knowledge with cultural heritage in Central Asian agricultural communities.